Susceptibility of Malaysian rice (Oryza sativa L.) cultivar to saline water submergence based on the morphological traits - Sazali, Syafiqah Alia (Universiti Sultan Zainal Abidin, 2021)
Saline water submergence is a newly emerge abiotic stress jeopardizing rice production especially for the rice fields located nearby or alongside coastal areas. The stress was caused by the intrusion of sea water into those rice fields causing flash flood mainly during monsoon season. The present study was conducted to evaluate susceptibility level of selected Malaysian rice cultivars to saline water submergence at seedling stage based on the morphological traits and survival rate. There were six genotypes involved in the study mainly IR64-Sub1 as submergence tolerant control, Pokkali as salinity tolerant control, IR64 as susceptible control and MR297, MR284 and MR253 as local rice cultivars, respectively. The experiment was conducted using split plot design with three replications. On the day 14 after germination, all rice seedlings were totally submerged of about one-meter depth in a polyethylene tank containing saline water at 0, 4, 8 and 12 dS/m for 14 days while the non-submerged plant was control of the experiment. Seedling growth attributes and survival rate were recorded before, right after de-submerged and 14 days after de-submerged. All genotypes however were susceptible to saline water submergence at 4, 8 and 12 dS/m. In contrast, under 0 dS/m, IR64-Sub1 recorded significantly higher survival rate at 83% as compared to MR284 (17%), MR297 (17%), Pokkali (8%), MR253 (0%) and IR64 (0%). All genotypes were not survived under saline submergence. Therefore, further phenotypic screening of rice genetic resources originated from or nearby coastal areas could be suggested in order to increase chance of identifying potentially tolerant genotype to saline water submergence.